If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 30 + -10x = 5(2p + -6) Reorder the terms: 30 + -10x = 5(-6 + 2p) 30 + -10x = (-6 * 5 + 2p * 5) 30 + -10x = (-30 + 10p) Solving 30 + -10x = -30 + 10p Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + -10x = -30 + -30 + 10p Combine like terms: 30 + -30 = 0 0 + -10x = -30 + -30 + 10p -10x = -30 + -30 + 10p Combine like terms: -30 + -30 = -60 -10x = -60 + 10p Divide each side by '-10'. x = 6 + -1p Simplifying x = 6 + -1p
| a^3-5a^2-16a+80=0 | | 45*2y=45 | | 4(6+3.2w)+7=60.2 | | 2(1)+1-3(1)+4= | | -12t+12t+-t+-11=3 | | 5(p-8)=-36+5p | | A(n)=2+(4-1)(-2.5) | | X+2x+x=32 | | 2(3x+6)=-36+30 | | h-h+h=7 | | 4t-t=18 | | 8(x-0.25)=4(2x-0.5) | | 5/34*17/20= | | 2q-5q+-9q=12 | | 5x-3=93 | | 0.20x+0.45(30)=25.5 | | 8-(3n-6)=9-4n | | (x-2)(x+1)=3 | | 11-2x=5(x+1)-7x | | t^6+6t^3-27=0 | | 9r+3=37r+7 | | 3(3+c)=2(c-7) | | k-2k+-7k=-18 | | 5x+21+3x=29 | | 10-2r=28 | | 3(n+1)-(7n-5)=-5n | | 2.33=(x-78)/3 | | 4+8=6+g | | a-18=7a | | 2(0)+0-3(0)+4= | | 0.11p+1.25y=8.62 | | 15t+-13t+-15=-19 |